Oral calcium tolerance test in the early diagnosis of primary hyperparathyroidism and multiple endocrine neoplasia type 1 in patients with the Zollinger-Ellison syndrome. Groupe de Recherche et d'Etude du Syndrome de Zollinger-Ellison. Issue 2 (August 1996) - Cadiot, G; Houillier, P; Allouch, A; Paillard, M; Mignon, M
Abstract : BACKGROUND: In patients with the Zollinger-Ellison syndrome, the exclusion of multiple endocrine neoplasia type 1 is of important clinical relevance. Its diagnosis often relies on the existence of primary hyperparathyroidism. AIM AND METHODS: To investigate the parathyroid function of patients with the Zollinger-Ellison syndrome by use of an oral calcium tolerance test to identify both hypercalcaemic and normocalcaemic primary hyperparathyroidism, and, accordingly, multiple endocrine neoplasia type 1. PATIENTS: Among 51 consecutive patients with the Zollinger-Ellison syndrome referred to us between 1988 and 1994, 28 had not been investigated for parathyroid function and were prospectively studied. RESULTS: The investigation of calcium metabolism was abnormal in nine patients. One displayed characteristic features of humoral hypercalcaemia of malignancy. The diagnosis of primary hyperparathyroidism was biologically established in eight patients (29%) and subsequently confirmed by the presence of hyperplasia of the parathyroid glands in the seven patients who underwent neck exploration. Three patients with primary hyperparathyroidism had fasting hyper-calcaemia but the other five had normal fasting serum total calcium concentration and the diagnosis of primary hyperparathyroidism was established by means of the oral calcium tolerance test. Primary hyperparathyroidism was demonstrated in the five patients in whom the diagnosis of multiple endocrine neoplasia type 1 had been previously established on other criteria than primary hyperparathyroidism. By contrast, in three patients, primary hyperparathyroidism, either hypercalcaemic (one patient) or normocalcaemic (two patients) was the sole criteria for the diagnosis of multiple endocrine neoplasia type 1. These results also suggest that primary hyperparathyroidism is present before or close to the time of Zollinger-Ellison syndrome diagnosis. CONCLUSION: Complete investigation of the parathyroid function with calcium calcium and parathyroid hormone concentrations.